Restoration of Five Digit Hand in Type III B & C Thumb Hypoplasia–A Game Changer in Surgical Management - G. Balakrishnan; S. Vijayaragavan; B. Somesh (Indian Journal of Plastic Surgery)
Background Hypoplasia of thumb is the second common congenital difference of the thumb, next only to duplication. It may occur as an isolated hand difference or as a part of radial longitudinal deficiency. In approximately 60% of these children, the radius shows hypoplasia. The incidence of thumb hypoplasia is one in 100,000 live births. In 50% of these children, the other hand will also have similar deficiency, although variable in severity. Hypoplasia of thumb has been classified into five major categories, according to the increasing severity of hypoplasia. Type III hypoplasia of thumb is characterized by skeletal hypoplasia involving the first metacarpal and carpometacarpal joint, absent intrinsic muscles and rudimentary extrinsic muscles. It was further subclassified into types A, B & C. Type III B, described by Manske and McCarroll, involves extensive deficiency of extrinsic and intrinsic musculature with aplasia of the metacarpal base. Type III C, described by Buck-Gramcko, has hypoplastic metacarpal head. Methods It is widely believed that reconstruction of Type III B & C hypoplastic thumb will not be functionally useful, and they are often included in the indications for pollicization in thumb hypoplasia. In India, we frequently come across parents, who are not willing to remove the hypoplastic digit. This forced us to find out a way to reconstruct the hypoplastic thumb into a functionally useful digit. We describe our surgical technique of reconstruction of hypoplastic thumbs and our experience in utilization of the technique in five children with Type III B & C hypoplasia of thumb. Carpometacarpal joint of thumb was reconstructed and stabilized with a toe phalangeal transfer in the first stage and an opponensplasty was done in the second stage to improve movement. Results In all the five operated children, our surgical technique yielded a stable thumb which was functional. The donor site morbidity was acceptable. The parents were satisfied with the appearance and functional improvement. Conclusion Surgical reconstruction of hypoplastic thumbs of Type III B & C is possible, and conversion of these poorly developed remnants into a useful digit by our surgical technique is a gamechanger in the management of thumb hypoplasia.